Finding wonders : three girls who changed science - Atkins, Jeannine, 1953- (Atheneum Books for Young Readers, 2017)
In this biographical novel in verse, three girls in different time periods grow up to make historical contributions to science. First Maria Merian debunked the belief that caterpillars sprung from the mud by documenting the metamorphosis of insects. A century later, Mary Anning helped her father collect stone sea creatures and discovered fossils that would change human understanding of the past. Finally, Maria Mitchell helped her mapmaker father explore the stars and discovered a brand new comet!